Impact of Artificial Intelligence on Vocational Training and Entrepreneurship in Africa - DIAWARA Daman-Guilé; BALLO Amidou (International Journal of Scientific Research and Innovative Studies, 2025)
The impact of artificial intelligence (AI) on vocational training and entrepreneurship in Africa is significant and multidimensional. AI is transforming teaching and learning methods, allowing for the personalisation of training according to the individual needs of learners. AI-based tools also facilitate access to quality educational resources, particularly in remote areas. From where the issue addressed: Impact of artificial intelligence on vocational training and entrepreneurship in Africa. In the field of entrepreneurship, the adoption of AI offers start-ups opportunities to improve operational efficiency, optimise decision-making processes, and respond more quickly to market needs. Entrepreneurs who integrate AI solutions into their business models can access new data sources , enabling them to identify trends and anticipate consumer demands. However, challenges remain, including limited access to technology and digital infrastructure, as well as the need for tailored training to develop the skills necessary for using AI. To maximise the positive impact of AI, it is crucial to encourage collaborative initiatives between the educational, entrepreneurial, and technological sectors. In conclusion, AI has the potential to transform vocational training and entrepreneurship in Africa, but a concerted approach is needed to overcome obstacles and fully leverage these opportunities. Keywords: Training, Entrepreneurship, Artificial Intelligence (AI), Africa, Digital Skills, Startups. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/480